الاساليب الكمية ودورها في اتخاذ القرارات الإستثمارية -دراسة حالة مجمع عمر بن عمر بولاية قالمة – (مجلة الواحات للبحوث والدراسات, 2021)
ملخص تهدف هذه الدراسة إلى إبراز دور محاكاة مونت كارلو كإحدى الأساليب الكمية الداعمة لتقييم المشاريع الإستثمارية، ومدى إسهامها في اتخاذ قرارات الإستثمار السليمة خاصة في ظل ظروف المخاطرة واللاتأكد، بما يمكن من تحقيق أكبر عائد ممكن في ظل محدودية الموارد وتباين درجة المخاطرة. وتحقيقا لهذا الغرض، تم تطبيق أسلوب محاكاة مونت كارلو في تقييم مشروع استثماري مقترح يتمثل في "إنتاج شتلات الطماطم"  بمجمع عمر بن عمر بقالمة، وقد أسفرت النتائج على قدرة محاكاة مونت كارلو على نمذجة حالات اللاتأكد، مما أضفى عليها طابع الفعالية في رصد أهم المتغيرات ومدى تأثيرها على جدوى المشاريع المقترحة، ليُعزَّز بذلك قرار قبول الإستثمار بهذا المشروع، نظرا لما يدره من عوائد مجزية.الكلمات الدالة:اساليب، كمية، محاكاة مونت كارلو, قرار الإستثمار, تقييم المشاريع, المخاطرة, اللاتأكد.   Abstract:  This study aims to show the role of Monte Carlo simulation as one of the quantitative methods in support of evaluating investment projects, and its contribution in making investment decisions, especially under risk and uncertainty, in order to achieve the largest possible return in light of limited resources and the degree of variation Taking the risk. To this end, the Monte Carlo simulation method was applied in the evaluation of a proposed investment project "production of tomato seedlings" at Benamor Complex in Guelma.The results yielded the Monte Carlo simulation’s ability to model uncertainty situations, which made it more effective in Monitoring the most important variables and the extent of their impact on the feasibility of the proposed projects, thus strengthening the decision to accept investment in this project, given the rewarding returns it generates. Key words:Method,quantitave, Monte Carlo Simulation, Investment Decision, Projects Evaluating, Risk, Uncertainty.